Passion for Putin’s Palace: Political Protests in Modern Russia - Skiperskikh, Aleksandr (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
In this article, the author analyzes the protest activity in Russia in January–February 2021. Protest activity came to Russia after A. Navalny’s investigation of V. Putin’s palace in Gelendzhik. Like the Belarusian protests in August 2021, the Russian protests were suppressed by the police. A feature of the Russian protests was their mass character. A large number of cities in almost all Russian regions were involved in the protest. Based on the data of secondary analysis, the author tries to give his own research of the Russian protest activity in January–February 2021. Protest activity in a number of Russian regions did not look accidental. One could observe protest activity in them before, but with a different agenda. The factor of unpopular government is of great importance in regional protests. The authorities no longer have the proper stock of legitimacy. This fully applies to the governors appointed by V. Putin, and, often, not directly related to the regions that have their own specificity. Case studies of protests in Russian regions show new trends. The protests are increasingly carnival-like. Power is ridiculed and discussed with irony. Familiar dialogue with the authorities is confirmed in various forms and languages of protest. From the author’s point of view, protest activity in Russia will increase by the fall of 2021. In September 2021, elections to the Russian Parliament are to be held. The author assumes that disappointment with the authorities in Russia will grow. The social base of new protests can be broader.

W artykule tym autor poddaje analizie ruchy protestu, które wystąpiły w Rosji pomiędzy styczniem a lutym 2021 r. Bezpośrednią przyczyną protestów było śledztwo przeprowadzone przez A. Navalnego dotyczące rezydencji prezydenta Federacji Rosyjskiej W. Putina w Gelendzhik. Podobnie jak na Białorusi w sierpniu 2021 r., tak i w Rosji, protesty zostały stłumione przez policję. Te ostatnie cechowały się masowym udziałem Rosjan, a do protestów doszło w wielu miastach na terenie całego kraju. W swym badaniu autor posłużył się danymi wtórnymi. Protesty, do których doszło w wielu rosyjskich regionach pomiędzy styczniem a lutym 2021 r. nie miały znamion przypadkowości. Protestującym nie podoba się polityka władz zarówno na poziomie centralnym, jak i na poziomie lokalnym. Władze w znacznym stopniu straciły legi tymację do sprawowania swych rządów. Proces ten znajduje odzwierciedlenie w nominacjach gubernatorskich, które są funkcją decyzji politycznych Kremla, często nieuwzględniających lokalnej specyfiki poszczególnych regionów kraju. Analiza wspomnianych protestów ukazuje wystąpienie nowych trendów. Protesty te coraz częściej przybierały formę heppeningu, gdzie uczestnicy wyśmiewali absurdy władzy przy pomocy humoru, kalamburów oraz innych zabaw językowych. Zdaniem autora, protesty w Rosji będą przybierać na sile na jesieni 2021 r. Ma to związek z wrześniowymi wyborami parlamentarnymi, które doprowadzą do wzrostu niezadowolenia z polityki władz rosyjskich.
Pasja do pałacu Putina. Protesty polityczne we współczesnej Rosji
Keywords: authority; Belarus; carnival; discourse; legitimacy; Navalny; Putin; regional protests; Russia; władza; Białoruś; karnawał; dyskurs; legitymizacja; Nawalny; Putin; protesty regionalne; Rosja